The Making of Resilience - Sameshima, Pauline (Journal of the Canadian Association for Curriculum Studies, 2020)
This special issue contains select refereed conference proposal abstracts of presentations planned for the cancelled Canadian Society for the Study of Education (CSSE) conference at Western University May 30-June 4, 2020. The abstracts represent paper presentations, round tables, symposia and panel presentations from the Canadian Association for Curriculum Studies (CACS) and CACS’ special interest groups including: the Arts Researchers and Teachers Society (ARTS), the Canadian Critical Pedagogy Association (CCPA), the Science Education Research Group (SERG), the Language and Literacy Researchers of Canada (LLRC), and the Regroupement pour l’étude de l’éducation francophone en milieu minoritaire (RÉÉFMM).